Pengelolaan Limbah Medis Padat Puskesmas Se-Kota Pekanbaru - Emy Leonita; Benny yulianto (Jurnal Kesehatan Komunitas, 2014)
The amount of medical waste comes from health facilities are expected more increasing. Based on Indonesia Health Profile 2008, amount of health centers reached 8,548 units. Management of medical waste from hospitals, health centers, clinics and medical laboratories in Indonesia is still under professional standards. In Pekanbaru city does not have accurate data on medical waste management in health centers, and therefore it necessary related research to see the extent of medical waste management health centers. This study aims to determine the medical waste management in health centers as the city of Pekanbaru. Type of research is descriptive qualitative, study was conducted in 20 health centers in Pekanbaru. The number of informants in this study were 21 people consisting of 20 holders of environmental health programs each health center and 1 holder of the environmental sanitation program at the City Health Office. Instrument research using in-depth interviews and observation sheets. Results reveal that a health center of Pekanbaru city has done a medical waste management ranging from segregation, collection, storage, transportation, yet at the stage of annihilation still less than the maximum. Constraints faced was funding the operation and maintenance personnel as well as there is no incinerator machine is not functioning properly